A mixed methods evaluation of the breastfeeding memory aide CHINS - Shotton, Lynette; Collins, Tracy; Cordier, Reinie; Chikwava, Fadzai; Steen, Mary (Wiley-Blackwell, 2024)
Breastfeeding rates remain persistently low in the United Kingdom (UK) despite wide‐scale rollout of UNICEF Baby Friendly Initiative training and accreditation. More must be done to ensure breastfeeding practitioners can provide effective support. The memory aide CHINS (Close, Head free, In‐line, Nose to Nipple and Sustainable) could help practitioners remember, recall, and apply breastfeeding theory in practice and this paper presents a UK evaluation of its impact. A concurrent, convergent mixed methods approach was adopted using Normalisation Process Theory (NPT) as an overarching framework. An online survey targeted breastfeeding practitioners and academics from the UK (n = 115). A sub‐set (n = 16) of respondents took part in qualitative focus groups. Survey data was subjected to descriptive and inferential statistical analysis, and the focus group data was analysed, using NPT. CHINS is widely used in breastfeeding education and practice largely because of its simplicity and ease of integration in everyday practice, as well as its sustained inclusion in UNICEF Baby Friendly Initiative training. CHINS has introduced a standardised approach to the principles of positioning for effective breastfeeding. Doing so has helped address inconsistencies and poor practice in this area, and CHINS plays a role in assisting practitioners in building confidence in their breastfeeding practice. More needs to be done to ensure the breastfeeding workforce develop and maintain the requisite skills to promote and support breastfeeding, including the role of memory aides such as CHINS in achieving this.